SUPPLY CHAIN PERFORMANCE OF ORGANIC VEGETABLES (EVIDENCE ON SMES IN MALANG CITY) - Irsyad Fauzi; Anisa Aprilia; Heptari Elita Dewi (Faculty of Animal and Agricultural Science, Diponegoro University, 2021)
The role of supply chain management strategies in the organic vegetable business is to createcompetitiveness by prioritizing fulfillment of consumer demand appropriately. One of the companiesengaged in the organic vegetable business in Malang City is Abang Sayur Organik (ABS) SMEs. Theorganic broccoli commodity is a superior product from ABS SMEs which continues supplied to retailand manufacture. Common problems that occur in the organic broccoli supply chain are fluctuations indemand and mismatches in the quality of products shipped. Measurement of supply chain performanceis needed to answer the existing problem. This study aims to describe the condition of supply chainmanagement and measure the performance of organic vegetable supply chains in ABS SMEs. The dataused are primary data obtained from questionnaires distributed to all ABS organic broccoli supply chainactors. Supply chain performance measurement uses the benchmark score method of Supply ChainOperation Reference (SCOR) performance indicators that include reliability, responsiveness, agility,costs, and assets with a value classification of parity, advantage, and superior. The results showed thatsupply chain actors involved were suppliers, distributors, manufacturers, retailers, and consumers.Measurement of Perfect Order Fulfillment performance indicators at the position of advantage at the supplier level and superior at the distributor level to retail. The value of Order Fulfillment Cycle Timeand flexibility are superior at each actor, while the value of inventory days of supply at the supplier,distributor and manufacturing level is at a position of advantage but at the retail level at a superiorposition. Cash To Cash Cycle Time value is superior position in each supply chain actor, but for theTotal Supply Chain Management Cost value in each organic broccoli supply chain actor is in a gap-parity position